2011
DOI: 10.1186/1471-2474-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the dopamine 1 and dopamine 5 receptors increase skeletal muscle mass and force production under non-atrophying and atrophying conditions

Abstract: BackgroundControl of skeletal muscle mass and force production is a complex physiological process involving numerous regulatory systems. Agents that increase skeletal muscle cAMP levels have been shown to modulate skeletal muscle mass and force production. The dopamine 1 receptor and its closely related homolog, the dopamine 5 receptor, are G-protein coupled receptors that are expressed in skeletal muscle and increase cAMP levels when activated. Thus we hypothesize that activation of the dopamine 1 and/or 5 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…It has been previously suggested that Drd1 , Glut4 , and Vmat2 are potential candidate genes for the regulation of physical activity [1], [6], [7], [8], [10], [13] with Glut4 in particular, showing a direct effect on activity when over expressed [11]. Thus, we were somewhat surprised that knockdown of both Drd1 and Glut4 simultaneously in soleus (Experiment 3) did not affect activity levels.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…It has been previously suggested that Drd1 , Glut4 , and Vmat2 are potential candidate genes for the regulation of physical activity [1], [6], [7], [8], [10], [13] with Glut4 in particular, showing a direct effect on activity when over expressed [11]. Thus, we were somewhat surprised that knockdown of both Drd1 and Glut4 simultaneously in soleus (Experiment 3) did not affect activity levels.…”
Section: Discussionmentioning
confidence: 67%
“…However, the rebound of Vmat2 observed in the soleus (Experiment 1 and 2) and nucleus accumbens (Experiment 2) along with the associated increase in physical activity could provide a potential explanation for the regulation of voluntary physical activity. It has been shown that the dopamine system in skeletal muscle affects muscle force production [8] and in the brain affects reward driven behavior [6]. When mice are given, artificial dopamine there is an associated hyperactivity response [50], [51], [54], [58].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations